Pemilihan Bahasa Etnik Bugis dalam Ranah Keluarga Berdasarkan Hubungan Peran dan Kategori Pekerjaan di Kabupaten Donggala - Tamrin Tamrin (Kantor Bahasa Provinsi Maluku Utara, 2017)
Language selection is a phenomenon that is common in multilingual societies. By taking the case of Bugis ethnic language selection in the family domain based on the relationship of roles and occupation categories in Donggala District, this study aims to (1) describe the pattern of Bugis ethnic language selection in the family sphere by occupation category and role relations in Donggala District, (2) to describe the influence of work on Bugis ethnic language election in Donggala District and (3) to analyze the factors underlying the selection of Bugis ethnic languages ​​in the family sphere by occupation category and role relations in Donggala District. The method used is a sociolinguistic approach with questionnaires, interviews, observations, and recording techniques, then analyzed based on the percentage pattern of Bugis ethnic language selection in the family realm. The result of the analysis shows that Bugis ethnic in Donggala Regency still dominantly choose Bugis language as communication tool in family domain based on the relation of role and occupation category. Respondents who work as civil servants / military / police and students who have a lower percentage in Bugisnya language electives.